Children with Hirschsprung's Disease and Syndromes with Cognitive Dysfunction: Manifestations, Treatment, and Outcomes - Hedbys, Josefine; Hasserius, Johan; Granéli, Christina; Arnbjörnsson, Einar; Hagelsteen, Kristine; Stenström, Pernilla (The Surgery Journal, 2019)
Introduction To assess differences in initial symptoms, treatments, and bowel function between children with Hirschsprung's disease (HD) with or without a cognitive dysfunction (CD).Materials and Methods The study included children with HD who underwent transanal endorectal pull-through. A retrospective chart review was performed to collect data on patient characteristics, diagnosis, and treatment. Data on bowel symptoms in children older than 4 years without a colostomy were compiled during a cross-sectional, patient-reported follow-up.Results Fifty-three children with HD were included; of these, 12 (23%) had CD. The median birth weight was lower, frequency of vomiting as the presenting symptom was lower, and time until the first contact with a pediatric surgeon was higher in children with CD than in those without (3,295 vs. 3,623 g, p = 0.013; 28 vs. 66%, p = 0.02; and 4 days vs. 1 day, p = 0.048, respectively). At follow-up, 5 (15%) of 33 children aged over 4 years had CD. More children without CD had some ability to hold back defecation and sense the urge to defecate than those with CD (p = 0.002 and p = 0.001, respectively).Conclusion HD children who have CD present with different initial symptoms, have a delay in the first consultation with a pediatric surgeon, and experience poorer bowel function outcomes than HD children without CD. Therefore, HD children with CD should receive special attention in both clinical practice and research.
Keywords: Hirschsprung's disease; pediatrics; bowel function; cognitive dysfunction; transanal endorectal pull-through; long-term outcome